2019
DOI: 10.1186/s12991-019-0247-1
|View full text |Cite
|
Sign up to set email alerts
|

Modeling human temperament and character on the basis of combined theoretical approaches

Abstract: Background Although there are several models on the structure of human temperament, character and personality, the majority follow a single approach, providing a unilateral and overly theoretical construct which is unsuitable for clinical application. The current study aimed to develop a complex and comprehensive model of temperament and character by empirically combining relevant existing theories. Methods The study included 734 hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 100 publications
1
7
0
Order By: Relevance
“…Our results appear to suggest an influence of faith, morality and personal motivation on efforts to decrease pornography use. Previous research has indicated that factors such as self-motivation, mindfulness, religiosity and spirituality positively influence mental health ( Yonker et al, 2012 ; Vitorino et al, 2018 ; Fountoulakis and Gonda, 2019 ; O’Driscoll et al, 2019 ). Additionally, higher levels of religiosity have been shown to be associated with a lower frequency of pornography consumption ( Poulsen et al, 2013 ; Perry and Hayward, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results appear to suggest an influence of faith, morality and personal motivation on efforts to decrease pornography use. Previous research has indicated that factors such as self-motivation, mindfulness, religiosity and spirituality positively influence mental health ( Yonker et al, 2012 ; Vitorino et al, 2018 ; Fountoulakis and Gonda, 2019 ; O’Driscoll et al, 2019 ). Additionally, higher levels of religiosity have been shown to be associated with a lower frequency of pornography consumption ( Poulsen et al, 2013 ; Perry and Hayward, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this cross-sectional study, we examined affective temperament among bank employees in relation to stress coping styles and job-related stress. TEMPS-A is commonly used for evaluation of affective temperament dimensions in clinical subgroups and in healthy subjects, 16,29,31 and CISS is an accepted tool for studying stress management strategies in different clinical groups. [32][33][34] Both questionnaires had good internal consistency in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…University students' mental health constitutes an area of special interest. This group is considered to belong to vulnerable groups and one reason is young age ( 1 ) but also the fact that any disruption during of the studies has deep long-term effects, plus that their personality is not mature enough to deal with additional stress ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%